Assessing an Online Patient Decision Aid about Upper Extremity Reconstructive Surgery for Cervical Spinal Cord Injury: Pilot Testing Knowledge, Decisional Conflict, and Acceptability - William Moritz; Amanda M. Westman; Mary C. Politi; DOD Working Group; Ida K. Fox (MDM Policy & Practice, 2023)
Background. While nerve and tendon transfer surgery can restore upper extremity function and independence after midcervical spinal cord injury, few individuals (∼14%) undergo surgery. There is limited information regarding these complex and time-sensitive treatment options. Patient decision aids (PtDAs) convey complex health information and help individuals make informed, preference-consistent choices. The purpose of this study is to evaluate a newly created PtDA for people with spinal cord injury who are considering options to optimize upper extremity function. Methods. The PtDA was developed by our multidisciplinary group based on clinical evidence and the Ottawa Decision Support Framework. A prospective pilot study enrolled adults with midcervical spinal cord injury to evaluate the PtDA. Participants completed surveys about knowledge and decisional conflict before and after viewing the PtDA. Acceptability measures and suggestions for further improvement were also solicited. Results. Forty-two individuals were enrolled and completed study procedures. Participants had a 20% increase in knowledge after using the PtDA ( P  < 0.001). The number of participants experiencing decisional conflict decreased after viewing the PtDA (33 v. 18, P  = 0.001). Acceptability was high. To improve the PtDA, participants suggested adding details about specific surgeries and outcomes. Limitations. Due to the COVID-19 pandemic, we used an entirely virtual study methodology and recruited participants from national networks and organizations. Most participants were older than the general population with a new spinal cord injury and may have different injury causes than typical surgical candidates. Conclusions. A de novo PtDA improved knowledge of treatment options and reduced decisional conflict about reconstructive surgery among people with cervical spinal cord injury. Future work should explore PtDA use for improving knowledge and decisional conflict in the nonresearch, clinical setting. Highlights People with cervical spinal cord injury prioritize gaining upper extremity function after injury, but few individuals receive information about treatment options. A newly created patient decision aid (PtDA) provides information about recovery after spinal cord injury and the role of traditional tendon and newer nerve transfer surgery to improve upper extremity upper extremity function. The PtDA improved knowledge and decreased decisional conflict in this pilot study. Future work should focus on studying dissemination and implementation of the ptDA into clinical practice.